ECONOMIC EMPOWERMENT: RESTRUCTURING AGRICULTURAL INDUSTRIAL MANAGEMENT (American Journal of Business Management, Economics and Banking, 2023)
This study explores the transformative potential of economic strategies and organizational restructuring within agricultural industrial management. It investigates the evolving landscape of agricultural enterprises, aiming to identify and implement mechanisms that enhance economic viability and operational efficiency. By scrutinizing various models and approaches, this research seeks to illuminate pathways for sustainable growth, empowering agricultural industries to navigate challenges, optimize resource utilization, and adapt to dynamic market demands. Through an interdisciplinary analysis of economic frameworks and organizational methodologies, this study endeavors to offer actionable insights for redefining the management paradigms of agricultural enterprises, fostering resilience, and fostering growth in the sector.